The Effect of Digital Payment on Generation Z's Consumptive Behaviour - Athalia Asta Dewi (International Journal Administration, Business & Organization, 2024)
This study aims to determine the effect of the QRIS digital payment tool on the consumer behaviour of Generation Z. The research involved 120 respondents who are students of the Bandung State Polytechnic, Indonesia. The research method used is quantitative descriptive, with data analysis techniques including descriptive and regression tests. Data were collected through questionnaires distributed via social media platforms and face-to-face interactions with the respondents. The study results indicate that QRIS has a 25.4% influence on the consumption behaviour of students at the Bandung State Polytechnic, who are part of Generation Z. In contrast, 74.6% of the influence on their consumption behaviour is attributed to other variables not examined in this research. These findings suggest that although QRIS influences the consumption behaviour of students, this influence is classified as low. Thus, this study provides insights into the role of QRIS in shaping the shopping habits of students in the current digital era. The results of this research can be a reference for marketers and digital product developers in designing more effective marketing strategies for Generation Z and understanding how they interact with digital payment technology.